(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article provides a philosophical analysis of the concepts of “emotion” and “will” in the context of artificial intelligence. These categories have traditionally defined the essence of human subjectivity: emotion as an inner affective response to the world, and will as the capacity for free and purposeful action. In AI, however, they are reduced to simulation — algorithmic reproduction of forms without inner content. Nevertheless, such resemblance acquires social significance: people interact with machines as if they were living partners. The paper discusses the philosophical and ethical consequences of this process and emphasizes the necessity of distinguishing between simulation and genuine experience, between function and ontology, in order to preserve the uniqueness of human freedom and responsibility.